Psychodynamic treatment of anorexia nervosa and bulimia / Craig Johnson - Johnson, Craig
"Early treatment literature on anorexia nervosa and bulimia reported almost exclusively on brief treatment approaches that entailed either psychopharmacological or cognitive-behavioral interventions. While this literature demonstrated that one-third of these patients were treatable with brief therapy and another one third showed improvement, the final one-third of these patients did not respond to brief interventions. Recent research indicates that this last group of patients may also suffer from significant personality disorders or Axis II co-morbidity. Considered difficult to treat, these patients require longer term, informed individual psychotherapy. Designed specifically to address the challenges of this difficult-to-treat population, this volume is the first to focus exclusively on exploring eating disorders from a psychodynamic perspective."--pub. description